Dystocia due to Post-Cervical Uterine Torsion along with Foetal Ascites in a Cross-Bred Holstein-Friesian Cow - Sharma, Pushkar; Mahour, Sobran Singh; Parihar, Atul Singh; Sankhla, Sachin; Khushwah, Neeraj (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A twisting or rolling of the uterus along its longitudinal axis is known as uterine torsion (Roberts, 2004). Compared to other domestic animal species, bovines have a significantly higher prevalence of dystocia (Dutt et al., 2021). Uterine torsion is one of the common causes of dystocia in buffaloes than in cows (Purohit et al., 2011). In dairy cattle frequency of right horn pregnancy is reported as 60% to 68%, counterclockwise torsion would then be detected primarily in cases of right horn pregnancy (Arthur et al., 1996). Blockage of lymphatics, excessive production or inadequate drainage of peritoneal fluid and other factors can result in foetal ascites (Sloss and Duffy, 1980). Additionally, dropsical conditions of foetus such as hydrocephalus, ascites, hydrothorax, and foetal anasarca can also result in dystocia (Purohit et al., 2006; Purohit et al., 2012). The management of dystocia caused by left side post-cervical torsion and foetal ascites is described in the current case study. The patient was successfully treated without any complications